Energy Poverty (Dis)Assembling Europe's Infrastructural Divide - Bouzarovski, Stefan (Springer Nature, 2018)
EVALUATE is a multi-sited study, involving extensive research across a variety of cities and countries. Focusing primarily on four Central and Eastern European cities (Budapest, Gdańsk, Prague and Skopje) the project has undertaken a customized survey with 2435 households, supplemented with insights from in-depth household interviews, 'energy diaries' and energy efficiency audits in the homes of approximately 160 households living in the four cities. EVALUATE has entailed 195 expert interviews in a much wider range of sites across the world, as well as an analysis of micro-data from national and European Union surveys of energy poverty. It has led to more than 200 dissemination activities, while laying the basis for the European Energy Poverty Observatory as well as a new European Co-operation for Science and Technology Action on 'European Energy Poverty: Agenda Co-Creation and Knowledge Innovation'